2005
DOI: 10.2320/matertrans.46.790
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced Martensitic Transformation and Superelasticity of Alloys: Experiment and Theory

Abstract: The superelasticity of alloys undergoing a stress-induced martensitic transformation is studied in both experimental and theoretical way. Experimental stress-strain dependencies illustrating the different types of superelastic behavior are taken from Ni-Mn-Ga alloys typifying thermoelastic martensites and then modeled theoretically using a statistical approach to describe the growth of stress-induced martensite in the matrix of parent (austenitic) phase. A good agreement between the experimental and theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Actually, in [31] this compression behavior for the <110> A oriented NiFeGaCo single crystal was modeled in terms of the direct relationship between the elastic interface stresses and the MT kinetics. Similar tendencies have been also observed in the experiments on the NiMnGa, CoNiGa and CoNiAl single crystals [17,20,37,38] which show a non-monotonous behavior for applied stress in the <110> direction, as occurs in our specimen.…”
Section: Temperature Of Ss Test Cyclesupporting
confidence: 90%
See 1 more Smart Citation
“…Actually, in [31] this compression behavior for the <110> A oriented NiFeGaCo single crystal was modeled in terms of the direct relationship between the elastic interface stresses and the MT kinetics. Similar tendencies have been also observed in the experiments on the NiMnGa, CoNiGa and CoNiAl single crystals [17,20,37,38] which show a non-monotonous behavior for applied stress in the <110> direction, as occurs in our specimen.…”
Section: Temperature Of Ss Test Cyclesupporting
confidence: 90%
“…In all experiments in Figure 1, where the stress-induced MT is observed, the curves show a non-monotone stress-strain dependence just after achieving the critical stress necessary for the transformation. Such non-monotone σ-ε dependencies of the forward and reverse stress-induced MT indicate the non-equilibrium progression of the transformation between the austenitic and martensitic phases and is linked to the different stresses required for the nucleation and propagation of the interfaces between phases [37]. Actually, in [31] this compression behavior for the <110> A oriented NiFeGaCo single crystal was modeled in terms of the direct relationship between the elastic interface stresses and the MT kinetics.…”
Section: Temperature Of Ss Test Cyclementioning
confidence: 99%
“…24 Recent work has also shown that external mechanical loads can induce phase switching at first order ferroelectric-to-paraelectric transitions, 19,25 similar to superelasticity in shape-memory alloys. 26 This behavior, however, has not been found in perovskite ferroelectrics with second order ferroelectric-to-paraelectric transitions, such as PZT compositions located near the morphotropic phase boundary. 27 In the case of BaTiO 3 , a number of previous experimental investigations have focused on the effect of hydrostatic pressure 13,28,29 and radial 20,30,31 stress on the dielectric properties and the Curie point of single crystal and polycrystalline materials.…”
mentioning
confidence: 99%
“…This explains the discrepancy in the stress levels predicted for the remaining cases. Regarding the negative slope in the experiment in case (iii), we note that there are explanations available in the literature for some superelastic materials [17], and in the present case we believe this is an artifact of the mechanical test apparatus, which operates in a condition that is neither exactly load-nor displacement-controlled.…”
mentioning
confidence: 57%
“…is the effective Young's modulus [17,18], E a and E m are the Young's moduli in the pure austenite and martensite, respectively, 0 is the equilibrium temperature between the two phases in the stress-free state, and is the latent heat. The nonlocal term can be viewed as the interface energy between the two phases.…”
mentioning
confidence: 99%